Optically monitored drug delivery patch based on porous silicon and polymer microneedles - Dardano, Principia (Biomed Opt Express, 2016)
Fabrication and characterization of an optically monitored hybrid patch for local administration of drugs, based on polymeric micro-needles and a porous silicon free-standing membrane, are reported. The micro-needles are realized by an innovative photolithographic approach that allows fine tuning of geometrical parameters, using polyethylene glycol and a commercial photo-catalyzer. The porous silicon multilayer not only increases the storage of a relevant amount of the drug, but also offers a continuous, naked-eye monitoring of the drug delivery process. As a proof-of-concept experiment, we report our results on the release of a dye molecule (fluorescein, 332 Da) in a phosphate saline buffer.